FENOMENA GAYA HIDUP ALA SELEBGRAM PADA MAHASISWA DI INSTAGRAM - Humaira Kamilah; Yanto Yanto; Sapta Sari (UNIVED PRESS, Universitas Dehasen Bengkulu, 2020)
The purpose of this research is to find out Celebgram (Celebrity on Instagram) lifestyle in college students on Instagram. This research uses a qualitative research method with a qualitative descriptive approach and this study uses the theory of lifestyle classification according to David Chaney (2007), which consists of several lifestyles namely, lifestyle industry, lifestyle advertising, public relations and lifestyle journalism, lifestyle independent and hedonic lifestyle. This research was conducted by interview, observation and documentation study data collection techniques. The subjects in this study were 5 students of Communication Science at Dehasen University of Bengkulu who were the followers of Instagram on Saritiw. The results of this study indicate that the lifestyle of Celebrity Instagram for students on Instagram is 4 out of 5 lifestyle classifications namely lifestyle industry, lifestyle advertising, public relations and lifestyle journalism, and hedonic lifestyle. Of the 4 lifestyle classifications, there is the most dominant lifestyle, namely the lifestyle industry. Because in this day and age the dependence on style is appearance / fashion that will continue to change. Then appearance is the most important thing for them to form a lifestyle. With the Saritiw style they followed on Instagram, they felt a change from their previous style.